2003
DOI: 10.1128/aac.47.2.739-746.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Macrolide Susceptibility on Efficacies of Clarithromycin and Azithromycin against Streptococcus pneumoniae in a Murine Lung Infection Model

Abstract: We evaluated the activities of clarithromycin and azithromycin against 19 isolates of Streptococcus pneumoniae using a neutropenic lung infection model. The isolates included five susceptible isolates (clarithromycin and azithromycin MICs, <0.12 g/ml), nine isolates exhibiting low-level, mefA-mediated resistance (clarithromycin and azithromycin MICs, 0.5 to 32 g/ml), and five isolates expressing high-level, ermB-mediated macrolide resistance (clarithromycin and azithromycin MICs, >64 g/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…However, there are few studies about the clinical outcome of pneumonia caused by erm B-mediated high-level MRSP. HOFFMAN et al [25] reported that CLR and AZM did not improve the survival rates. In contrast, in the present immunocompetent mouse model, CLR and AZM were effective even against high-level MRSP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few studies about the clinical outcome of pneumonia caused by erm B-mediated high-level MRSP. HOFFMAN et al [25] reported that CLR and AZM did not improve the survival rates. In contrast, in the present immunocompetent mouse model, CLR and AZM were effective even against high-level MRSP.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the doses of CLR and AZM were chosen to achieve target parameters similar to those observed in healthy humans [25]. Nevertheless, neither CLR nor AZM reduced the viable number of pneumococci lower than control in murine lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, none of the macrolides tested in this study were able to protect mice from bloodstream invasion by macrolide-resistant S. pneumoniae, which resulted in the death of all infected mice. In neutropenic mice, however, the efficacy of CLR and AZM against clinical isolates of macrolide-resistant S. pneumoniae varied with the level of macrolide resistance of the pathogen (20), which indicates that the enhancement of local resistance against macrolideresistant S. pneumoniae by sub-MIC levels of macrolide compounds may require an immunocompetent status of the hosts. Furthermore, this fact strongly suggests that the direct antimicrobial activity of macrolides should be necessary for complete protection against a high level of macrolide-resistant S. pneumoniae, regardless of the degree of innate immunity in the hosts.…”
Section: Vol 51 2007 Macrolides and Resistant S Pneumoniae 1749mentioning
confidence: 98%
“…Because intracellular concentrations of macrolide antibiotic often exceed the MIC of phagocytized pathogens, macrolides have also been demonstrated to be effective against microorganisms with in vitro macrolide resistance [35,36]. The excellent intracellular penetration of macrolides also appears to explain their effectiveness against intracellular pathogens [34].…”
Section: Effects On Host-pathogen Interactionsmentioning
confidence: 99%